2010
DOI: 10.1152/ajpregu.00675.2009
|View full text |Cite
|
Sign up to set email alerts
|

Expression of heat shock proteins in anoxic crucian carp (Carassius carassius): support for cold as a preparatory cue for anoxia

Abstract: The crucian carp (Carassius carassius) tolerates anoxia for days to months depending on temperature. During episodes of stress, heat shock proteins (HSPs) are important for limiting cellular damage, mainly by ensuring protein function. Accordingly, we hypothesized that anoxia would change the expression of HSPs and that this response would be temperature dependent. Real-time RT-PCR was used to investigate the effects of 1 and 7 days anoxia (A1 and A7) on the expression of HSP70a, HSP70b, HSC70, HSP90, and HSP3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 63 publications
1
31
1
Order By: Relevance
“…Low temperature pre-conditions cardiac E-C coupling for winter by altering gene activity Although the significance of low temperature in adjusting crucian carp physiology for winter anoxia is documented by several previous studies (Vornanen, 1994b;Tiitu and Vornanen, 2001; Rissanen et al, 2006;Stensløkken et al, 2010;Varis et al, 2016), this is the first study to examine the effects of temperature and anoxia on transcript expression of E-C coupling genes. Comparison of expression data between summer-and winter-acclimatised crucian carp indicates large differences in the activity of genes contributing to the molecular machinery of cardiac E-C coupling, similar to previous reports for crucian carp acclimated to different temperatures in the laboratory (Hassinen et al, 2008b(Hassinen et al, , 2011Korajoki and Vornanen, 2014).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Low temperature pre-conditions cardiac E-C coupling for winter by altering gene activity Although the significance of low temperature in adjusting crucian carp physiology for winter anoxia is documented by several previous studies (Vornanen, 1994b;Tiitu and Vornanen, 2001; Rissanen et al, 2006;Stensløkken et al, 2010;Varis et al, 2016), this is the first study to examine the effects of temperature and anoxia on transcript expression of E-C coupling genes. Comparison of expression data between summer-and winter-acclimatised crucian carp indicates large differences in the activity of genes contributing to the molecular machinery of cardiac E-C coupling, similar to previous reports for crucian carp acclimated to different temperatures in the laboratory (Hassinen et al, 2008b(Hassinen et al, , 2011Korajoki and Vornanen, 2014).…”
Section: Discussionmentioning
confidence: 90%
“…Lowering temperature is the seasonal cue that usually pre-conditions these fish for winter, e.g. by stimulating glycogen storage and modifying the cardiac excitation-contraction (E-C) coupling machinery (Tiitu and Vornanen, 2001;Rissanen et al, 2006;Stensløkken et al, 2010;Varis et al, 2016). The heart of summer-acclimatised crucian carp responds to short-term oxygen shortage (1-16 h) at +20°C with a strong bradycardic reflex, which is mediated by increased cholinergic tone (Vornanen, 1994b;Vornanen and Tuomennoro, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that crucian carp use low temperature as a preparatory cue for anoxia (77). For example, the expression of the cytoprotective heat shock protein HSP70 increases in anoxia in warm acclimated fish, whereas it is already increased in normoxia in cold acclimated fish (70). This is especially interesting, because nitrite has been found to upregulate the expression of HSP70 (7).…”
Section: R471 No Metabolites In Anoxic Crucian Carpmentioning
confidence: 99%
“…Expression of all genes showed anoxia-induced changes varying in size and direction, as well as with organ and temperature. 61 For example, hsp70a transcripts increased ∼10-fold in the brain and heart after 7 hours of anoxia at 13°C whereas hsc70 increased after 1 hour of anoxia in both organs at both temperatures. Of particular interest, normoxic fish showed 7-and 11-fold higher expression of hsp70a in both organs in cold (8°C) compared with warm (13°C) water.…”
mentioning
confidence: 92%
“…61 Anoxia tolerance allows carp to survive in ice-locked small ponds that become oxygen-depleted over the winter months. A unique metabolic strategy aids their survival; carp avoid metabolic poisoning by lactic acidosis by catabolizing lactate to ethanol and CO 2 that are both excreted.…”
mentioning
confidence: 99%